Keanekaragaman Larva Diptera di Sungai Logawa Kabupaten Banyumas - Eti Wahyuningsih -; Lu’lu’ul Ma’rifah (JURNAL BIOSHELL, 2022)
This study aims to determine the diversity of Diptera Larvae in the Logawa River, Karang Lewas District, Banyumas Regency. This research was conducted in June-August 2021. Located in the Logawa River area, Banyumas Regency. This study used a survey method, sampling was carried out 3 times within a month. The sampling method is purposive random sampling, namely the research station is selected based on certain criteria. There are 5 observation stations, Station 1 in Sunyalangu, Station 2 in Dawuhan Wetan and Station 3 in Karanglewas Lor, Station 4 in Karanglewas Kidul, and Station 5 in Patikraja. The results of this study obtained 8 species, namely Baetis Fuscatus, Dicrotendipes septemmaculatus, Hydropsychidae Ceumatopsike, Isoperia Orata, Mecistogaster simpleta, Stenelmis canaliculata, Baetis Tricoudatus, and Thysanura sp. There are two categories of diversity, namely the low category and the medium category. The highest diversity was found at station 1 with a diversity index value of 1.64, the diversity index value was included in the medium category. The lowest diversity was found at station 2 with a diversity index value of 0.00. There are two dominant categories, namely low and medium categories. The highest dominance is found at station 5 with a dominance index value of 0.56, the dominance index value is included in the medium category. The lowest dominance is at station 3 with an index value of 0.00, the index value is included in the low category. The highest similarity index value is at station 5 with an index value of 0.21, and the lowest similarity index value is at station 3 with an index value of 0.00.